ANALISIS PELAKSANAAN PEMERIKSAAN PAJAK STUDI KASUS PADA KANTOR PELAYANAN PAJAK (KPP) PRATAMA MAROS - Riza Nurfadilah; Nurul Afifah; Ilham Ilham (JURNAL PABEAN : PERPAJAKAN BISNIS EKONOMI AKUNTANSI MANAJEMEN, 2021)
The purpose of this research is to determine the implementation of tax audits conducted by Tax Service Office Pratama Maros.  The research method used is descriptive qualitative data analysis.  The results of this study indicate that, in the implementation of tax audits at Tax Service Office Pratama Maros, there are several stages starting from the assignment of instructions, the preparation stage which consists of: examining and studying taxpayer data to preparing facilities and infrastructure before conducting the audit.  Furthermore, the Implementation Stage which consists of: Examining the place where the business is required to establish until the Final Discussion on the Audit Results and the Reporting Issuance Stage which consists of the preparation of audit working papers (KKP) to the preparation of tax audit reports and finally the return of taxpayer documents that have been borrowed during the process  examination.  This examination is in accordance with the Regulation of the Minister of Finance Number 184 / PMK.03 / 2015 Regarding Audit Procedures Keyword:Implementation, Audit Tax